2020
DOI: 10.1002/jso.26124
|View full text |Cite
|
Sign up to set email alerts
|

Sacroiliac joint cut accuracy: Comparing new technologies in an idealized sawbones model

Abstract: Background and Objectives: The anatomical complexity of the pelvis creates challenges for orthopaedic oncologists to accurately and safely resect tumors involving the sacroiliac joint. Current technology may help overcome these obstacles. Methods: Four fellowship-trained orthopaedic oncologists performed 22 all-posterior sacroiliac cuts using freehand, computerized navigation, and patient-specific cutting guides on a Sawbones male pelvis model. Cut accuracies to preoperative planned margins were analyzed via a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Both in vitro and in vivo studies have shown that the use of PSI confers superior cut precision over freehand osteotomy and comparable precision to navigation techniques 4,28,29 . Moreover, cadaveric studies have demonstrated improved efficiency with the use of PSI over both freehand and navigation techniques, 30 aligning with our previous work using a sawbones model which found that the improved precision afforded by 3D‐printed PSI technology led to less damage to simulated pelvic viscera 31 …”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Both in vitro and in vivo studies have shown that the use of PSI confers superior cut precision over freehand osteotomy and comparable precision to navigation techniques 4,28,29 . Moreover, cadaveric studies have demonstrated improved efficiency with the use of PSI over both freehand and navigation techniques, 30 aligning with our previous work using a sawbones model which found that the improved precision afforded by 3D‐printed PSI technology led to less damage to simulated pelvic viscera 31 …”
Section: Discussionsupporting
confidence: 66%
“…4,28,29 Moreover, cadaveric studies have demonstrated improved efficiency with the use of PSI over both freehand and navigation techniques, 30 aligning with our previous work using a sawbones model which found that the improved precision afforded by 3D-printed PSI technology led to less damage to simulated pelvic viscera. 31 In recent years, our institution has made a gradual transition away from freehand resection for internal hemipelvectomy in favor of computer navigation and novel 3D-printed PSI designs (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the main body alone was not enough to correctly position the SCG. Therefore, added positioning features were added that were similar to what Siegel et al (2020 ), Evrard et al (2019 ), and Cernat et al (2016 ) recommended. These positioning features were added preferably in accessible areas of the bone to limit additional dissection, and their width can be limited to a maximum defined by the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…It produced accurate printing of the SCGs. It is also the most popular choice in pelvic resection guides in the literature ( Cartiaux et al, 2014 ; Gouin et al, 2014 ; Wong et al, 2015 ; Jentzsch et al, 2016 ; Sallent et al, 2017 ; Evrard et al, 2019 ; Siegel et al, 2020 ). PA12 was the material selected for this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation